Protein Disulfide Isomerase Regulates Endoplasmic Reticulum Stress and the Apoptotic Process during Prion Infection and PrP Mutant-Induced Cytotoxicity - Wang, Shao-Bin (Public Library of Science, 2012)
BACKGROUND: Protein disulfide isomerase (PDI), is sorted to be enzymatic chaperone for reconstructing misfolded protein in endoplasmic reticulum lumen. Recently, PDI has been identified as a link between misfolded protein and neuron apoptosis. However, the potential for PDI to be involved in the pathogenesis of prion disease remains unknown. In this study, we propose that PDI may function as a pleiotropic regulator in the cytotoxicity induced by mutated prion proteins and in the pathogenesis of prion diseases. METHODOLOGY/PRINCIPAL FINDINGS: To elucidate potential alterations of PDI in prion diseases, the levels of PDI and relevant apoptotic executors in 263K infected hamsters brain tissues were evaluated with the use of Western blots. Abnormal upregulation of PDI, Grp78 and Grp58 was detected. Dynamic assays of PDI alteration identified that the upregulation of PDI started at the early stage and persistently increased till later stage. Obvious increases of PDI and Grp78 levels were also observed in cultured cells transiently expressing PrP mutants, PrP-KDEL or PrP-PG15, accompanied by significant cytotoxicities. Excessive expression of PDI partially eased ER stress and cell apoptosis caused by accumulation of PrP-KDEL, but had less effect on cytotoxicity induced by PrP-PG15. Knockdown of endogenous PDI significantly amended cytotoxicity of PrP-PG15, but had little influence on that of PrP-KDEL. A series of membrane potential assays found that apoptosis induced by misfolded PrP proteins could be regulated by PDI via mitochondrial dysfunction. Moreover, biotin-switch assays demonstrated active S-nitrosylted modifications of PDI (SNO-PDI) both in the brains of scrapie-infected rodents and in the cells with misfolded PrP proteins. CONCLUSION/SIGNIFICANCE: Current data in this study highlight that PDI and its relevant executors may function as a pleiotropic regulator in the processes of different misfolded PrP proteins and at different stages during prion infection. SNO-PDI may feed as an accomplice for PDI apoptosis.